An atomic carbon source for high temperature molecular beam epitaxy of graphene - Albar, J.D.; Summerfield, Alex; Cheng, Tin S.; Davies, Andrew; Smith, E.F.; Khlobystov, Andrei N.; Mellor, C.J.; Taniguchi, Takashi; Watanabe, Kenji; Foxon, C.T.; Eaves, Laurence; Beton, Peter H.; et al. (Nature Publishing Group, 2017)
We report the use of a novel atomic carbon source for the molecular beam epitaxy (MBE) of graphene layers on hBN flakes and on sapphire wafers at substrate growth temperatures of ~1400 °C. The source produces a flux of predominantly atomic carbon, which diffuses through the walls of a Joule-heated tantalum tube filled with graphite powder. We demonstrate deposition of carbon on sapphire with carbon deposition rates up to 12 nm/h. Atomic force microscopy measurements reveal the formation of hexagonal moiré patterns when graphene monolayers are grown on hBN flakes. The Raman spectra of the graphene layers grown on hBN and sapphire with the sublimation carbon source and the atomic carbon source are similar, whilst the nature of the carbon aggregates is different - graphitic with the sublimation carbon source and amorphous with the atomic carbon source. At MBE growth temperatures we observe etching of the sapphire wafer surface by the flux from the atomic carbon source, which we have not observed in the MBE growth of graphene with the sublimation carbon source.